Perawatan Bibit Mangrove Pasca Penanaman Pada Kawasan Rehabilitasi Pesisir di Desa Tapulaga Kecamatan Soropia Kabupaten Konawe - Hasan Eldin Adimu; Indriyani Nur; Laifa Fekri; Farid Yasidi; Dewi Nurhayati Yusuf; Kadir Sabilu (PUSAKA ABDIMAS, 2025)
Community-based mangrove forest management is one of the management strategies that can increase efficiency and fairness in the utilization and management of natural resources. Stages of activities to overcome problems Stage I: Counseling, Counseling is carried out to provide initial information about mangrove ecosystem management and its handling Stage II: Monitoring and Evaluation, Monitoring and evaluation activities are always carried out every period even though the year ends. Monev is carried out after the activity to ensure that the activity continues and develops Therefore, efforts are needed to develop community participation in restoring the function and benefits of damaged mangrove forests in the implementation and supervision.